Enzyme Activity Regarding Sugar and Organic Acid Changes during Developmental Stages in Rainfed Fig (Ficus carica L.cv Sabz). Issue 1 (2nd January 2018) - Sedaghat, Sahar; Rahemi, Majid
ABSTRACT: The aim of this study was to assess the effects of invertase and amylase enzyme activities on starch, individual sugars, and organic acid changes during developmental stages (before caprification, fruit set, softening, and senescence) in Ficus carica L.cv Sabz with three replicates. The initial stage of fruit development showed the highest stored carbohydrates and the lowest total sugar and whilst the senescence stage obtained the lowest stored carbohydrates and the highest total sugar. Furthermore, high-performance of liquid chromatograph analysis revealed that the value of glucose and fructose significantly increased as fruits developed. Citric acid was the most abundant organic acid followed by malic acid. Moreover, invertase activity increased sharply before the caprification stage up to the senescence stage. We found that fig fruit possess α- and β-amylase activities, which increased dramatically up to the ripening stage and then slightly decreased at the senescence stage. The present study showed that this cultivar is a rich fruit based on glucose and fructose as well as citric and malic acid.